PEMBARUAN HUKUM ZAKAT DALAM UNDANG-UNDANG ZAKAT - Alamudi, Ichwan Ahnaz; Hasan, Ahmadi (Program Studi Manajemen Zakat dan Wakaf, 2022)
In the management of zakat, it is very necessary to have a clear legal umbrella in the form of regulations on zakat which are the basis for zakat management. Along with the times, the existing regulations are sometimes considered no longer accommodate the problem of zakat management in the field. Therefore, the latest regulations on zakat management are needed. This paper aims to try to discuss various legal reforms regarding zakat, especially in the zakat law. This study uses a juridical-normative approach, which is an approach based on legislation, theories, and concepts related to the legal scope of regulations in the field of zakat. The results of the study show that there are various regulations regarding zakat, ranging from Ministerial Regulations, Presidential Regulations, Government Regulations to Laws. And the new law on zakat management was born when the age of independence of the Unitary State of the Republic of Indonesia was quite old, namely 54 years. This is marked by the birth of Law no. 38 of 1999 concerning Management of Zakat. In its development, Law Number 38 of 1999 was revised to achieve optimization of zakat management in Indonesia. The result of the revision was the establishment of Law Number 23 of 2011 concerning Zakat Management. This was followed by the issuance of Government Regulation of the Republic of Indonesia Number 14 of 2014 concerning the Implementation of Law Number 23 of 2011 concerning Management of Zakat. Dalam pengelolaan zakat sangat diperlukan adanya suatu payung hukum yang jelas berupa peraturan tentang zakat yang menjadi landasan dalam pengelolaan zakat. Seiring dengan perkembangan zaman, peraturan yang ada terkadang dianggap tidak lagi mengakomodir persoalan pengelolaan zakat di lapangan, Oleh karena itu dibutuhkan peraturan-peraturan terbaru tentang pengelolaan zakat. Tulisan ini bertujuan untuk mencoba membahas mengenai berbagai pembaruan hukum mengenai zakat khususnya dalam undang-undang zakat. Penelitian ini menggunakan pendekatan yuridis-normatif, yaitu pendekatan yang didasarkan pada peraturan perundang-undangan, teori-teori, dan konsep-konsep berhubungan dengan cakupan hukum mengenai regulasi-regulasi pada bidang zakat. Hasil penelitian menunjukkan bahwa terdapat berbagai peraturan tentang zakat, mulai dari Peraturan Menteri, Peraturan Presiden, Peraturan Pemerintah hingga Undang-undang. Dan Undang-undang tentang pengelolaan zakat baru lahir di saat usia kemerdekaan Negara Kesatuan Republik Indonesia tergolong cukup tua yaitu 54 tahun. Hal tersebut ditandai dengan lahirnya Undang-Undang No. 38 Tahun 1999 tentang Pengelolaan Zakat. Pada perkembangannya Undang-undang Nomor 38 Tahun 1999 direvisi untuk mencapai optimalisasi pengelolaan zakat di Indonesia. Hasil dari revisi tersebut adalah dengan dibentuknya Undang-undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat. Disusul dengan terbitnya Peraturan Pemerintah Republik Indonesia Nomor 14 Tahun 2014 tentang Pelaksanaan Undang undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat.